A descriptive study on the prevalence of betel nut-chewing in Barangay Samoki, Bontoc, Mt. Province - General, Vanessa A.; Yutuc, Norleen; Galban, Angelita (Adviser).
This study aimed to determine the prevalence of betel nut chewing in Barangay Samoki, Bontoc, Mt. Province. A descriptive study design was used. A house-to-house interview was done to achieve the maximum mumber of subjects. Data regarding betel nut chewing practices were inquired such as frequency, duration, longevity, ingredients, influences and reasons for use. The age, gender, oral hygiene practices, and social history of the subjects were also noted. Results showed that there is a 6.3% prevalence of betel nut chewing among 634 surveyed residents of Barangay Samoki, Bontoc, Mt. Province.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Betel nut